Male Breast Cancer: An Updated Review of Epidemiology, Clinicopathology, and Treatment. (24th May 2022) - Zheng, Guoliang; Leone, Jose Pablo
Abstract : Male breast cancer (MaBC) is a rare clinical entity, which makes up approximately 1% of all breast cancers. However, the incidence of MaBC has been steadily increasing over the past few decades. The risk factors for MaBC include age, black race, family history of breast cancer, genetic mutations, liver cirrhosis, and testicular abnormalities. The majority of patients with MaBC present with painless lumps, and about half of the patients have at least one lymph node involved at the time of diagnosis. The treatment of MaBC models that of female breast cancer (FeBC), but this is mainly due to lack of prospective studies for MaBC patients. The treatment modality includes surgery, adjuvant radiation, endocrine therapy, and chemotherapy. However, there are some distinct features of MaBC, both clinically and molecularly, that may warrant a different clinical approach. Ongoing multinational effort is required, to conduct clinical trials for MaBC, or the inclusion of MaBC patients in FeBC trials, to help clinicians improve care for MaBC patients.